Expansion of IIMs: myths, realities and policy choices - Gupta, Ramesh (2006)
This article suggests a roadmap for IIM Ahmedabad to increase its student intake substantially within all available resources offered by its flagship programme, i.e., the postgraduate programme in management. A broadly similar solution for other IIMs could be worked out, as all share a similarity in programmes offered, in ethos and culture; any differences that exist would be in the details. - Reproduced.
Keywords: Indian Institute of Management